Characterization of geogrid mechanical and chemical properties from a thirty-six year old mechanically-stabilized earth wall. Issue 6 (December 2020) - Leshchinsky, Ben; Berg, Ryan; Liew, Willie; Kawakami-Selin, Morgan; Moore, Jaxom; Brown, Sophie; Kleutsch, Bernard; Glover-Cutter, Kira; Wayne, Mark
Abstract: The mechanical properties of geosynthetic reinforcements are known to be time-, environment- and stress-dependent. Characterization of these reinforcement properties is often assessed under controlled laboratory settings and extrapolated to the design life of geosynthetic-reinforced soil structures. However, despite the wide application of geosynthetic reinforcement in earth retaining structures, there is limited evaluation of how mechanical properties of geosynthetic materials change in situ on constructed works; and primarily limited to case studies within the first decade following construction. This study describes the change in mechanical properties of geogrids retrieved from the facing of the wrapped-face of one of the oldest geosynthetic-reinforced mechanically-stabilized earth (MSE) walls in the United States, constructed in 1983 in a relatively harsh, coastal environment. Laboratory characterization of mechanical and chemical properties of the geogrid are presented, and compared to properties of archived samples, as well as samples from another structure exhumed 8 and 11 years after its respective construction. The laboratory test results demonstrate that the geogrid mechanical and chemical properties have not significantly changed in the 35+ years of service. While the data from this study represents a limited set of conditions, these results demonstrate that geogrids may perform well long after construction. Highlights: Properties of geogrid samples extracted from a 36 year-old mechanically stabilized earth wall were characterized and compared to original specifications. Mechanical testing reflects that limited change has occurred in creep and tensile properties of the in-service geogrid. Modest changes in chemical properties are observed in the exposed geogrid in comparison to an archived sample, but still reflect serviceability.